The commissar : Aleksandr Askoldov - Grinberg, Marat, 1977- (KinoSputnik, 2016)
"Filmed in 1966 and 1967, but kept from release for twenty years, The Commissar is unquestionably one of the most important and compelling films of the Soviet era. Based on a short story by Vasily Grossman... This book is the first companion to the film. It recounts the film's plot and turbulent production history, and it also offers a close analysis of the artistic vision of its director, Aleksandr Askoldov..."--Page 4 of cover.